Pengaruh Konten Marketing, Kepercayaan dan Brand Image Terhadap Keputusan Pembelian Skincare Glad2Glow pada Gen Z di Tiktikshop - Rizki Wulanita Batubara; Ayu Sartika Siregar; Shofyan Roni (Digital Business Progress, 2026)
This study aims to analyze the influence of marketing content, trust, and brand image on the purchasing decisions of Glad2Glow skincare among Generation Z on TikTok Shop through a qualitative approach. The research method used is descriptive qualitative with data collection techniques through in-depth interviews, observation, and documentation of Generation Z informants who actively use TikTok and have been exposed to or purchased the skincare product. The results show that interesting, informative, and authentic marketing content plays a role in shaping consumers' initial interest. Consumer trust is formed through information transparency, honest reviews, and seller credibility, which function to reduce the perception of risk in online purchases. Meanwhile, a positive brand image provides a sense of security, strengthens confidence, and builds emotional closeness with consumers. These three variables are interrelated and shape the gradual purchasing decision process in Generation Z.